Nikah Muda : Antara Solusi Versus Belenggu Patriarki (Studi Kasus di Desa Bandang Laok Bangkalan) (International Forum of Researchers and Lecturers, 2023)
The meaning of customs and traditions passed down from ancestors is something that is difficult to just leave even though times have changed because they are deeply rooted and practiced continuously. One example is early marriage among the Madurese community, especially in Bandang Laok Bangkalan Village. Among the Madurese, their children, especially girls, choose to get married immediately rather than continue their studies or work. This study aims to find out how the perspectives of the Madurese people and ordinary people regarding early marriage in Madura, where this phenomenon is still common, especially in rural areas. The researcher also relates it to the Symbolic Interactionism Theory with the concept of mind, self and society to be analyzed from a sociological point of view. In this study, researchers used literature studies to obtain data and indirect observations. The results of this study are that this phenomenon is a real form of human unconsciousness about themselves, maybe they agree about arranged marriages carried out by their parents or family, but actually they are also depressed.